The effects of crocetin supplementation on the blastocyst outcome, transcriptomic and metabolic profile of in vitro produced bovine embryos - dos Santos, E. C.; Varchetta, R.; de Lima, C. B.; Ispada, J.; Martinho, H. S.; Fontes, P. K. [UNESP]; Nogueira, M. F.G. [UNESP]; Gasparrini, B.; Milazzotto, M. P. (Elsevier, 2019)
The earliest stages of embryo development are deeply influenced by reactive oxygen species (ROS), byproducts of the mitochondrial oxygen metabolism that play a key role as messengers in normal cell signal transduction and cell cycling. Despite its positive roles, the imbalance caused by the excess of ROS and an inefficient antioxidant system leads to oxidative stress, with negative consequences to the cell such as DNA damage, metabolic changes, mitochondrial stress and cell death. In the present work, crocetin - a natural antioxidant - was added to the culture media of bovine embryos to evaluate the efficiency of its antioxidant capability during embryo culture. Oocytes were in vitro matured (IVM) and fertilized according to standard protocols. Embryos were cultured at 38.5 °C under humidified air with 5% CO2, 7% O2, and 90% N2 in Synthetic Oviduct Fluid (SOF) medium supplemented with amino acids and either 5% of FBS (SOFaa) (control group) or SOFaa supplemented with 1 μM crocetin (crocetin group). After 5 days from the beginning of in vitro culture (IVC) (day 5 - D5), embryos were transferred to individual drops of culture media. At day 7 (D7), embryos were assessed by means of blastocyst rates, morphophysiological analyzes (total cell number, ROS and mitochondrial activity levels), transcript quantitation of 47 genes and metabolomic evaluation of the culture media by Raman spectroscopy. In the crocetin group blastocyst rates were higher and embryos had increased total cell number and decreased intracellular levels of ROS. These embryos also had upregulation of genes related with response to stress and lipid metabolism (ATF4, BAX, FOXO3, GADD45A, GPX1, GPX4, HSF1, SOD2, ACACA, SREBF1 and SREBF2). Raman spectroscopy corroborated these results indicating more active lipid and amino acid production in this group. The absence of crocetin in the culture media resulted in higher ROS level, as well as up regulation of genes related to DNA damage, stress response and energy metabolism (MORF4L2, SOD1, TXN, PFKP, PGK1 and PPARGC1A). In conclusion, crocetin supplementation during culture protects embryos from oxidative stress and influences the adaptive response to stress conditions, leading to an increase in both blastocyst yield and quality, as well as changes in transcriptomic and metabolic profile of in vitro produced bovine embryos.
Keywords: Antioxidant; Bovine; Crocetin; Embryo culture; Embryo quality; Metabolism